Rational design of multifunctional micelles against doxorubicin-sensitive and doxorubicin-resistant MCF-7 human breast cancer cells - Hong, Wei (Int J Nanomedicine, 2017)
Even though a tremendous number of multifunctional nanocarriers have been developed to tackle heterogeneous cancer cells, little attention has been paid to elucidate how to rationally design a multifunctional nanocarrier. In this study, three individual functions (active targeting, stimuli-triggered release and endo-lysosomal escape) were evaluated in doxorubicin (DOX)-sensitive MCF-7 cells and DOX-resistant MCF-7/ADR cells by constructing four kinds of micelles with active-targeting (AT-M), passive targeting, pH-triggered release ((pH)T-M) and endo-lysosomal escape ((endo)E-M) function, respectively. AT-M demonstrated the strongest cytotoxicity against MCF-7 cells and the highest cellular uptake of DOX due to the folate-mediated endocytosis. However, AT-M failed to exhibit the best efficacy against MCF-7/ADR cells, while (endo)E-M exhibited the strongest cytotoxicity against MCF-7/ADR cells and the highest cellular uptake of DOX due to the lowest elimination of DOX from the cells. This was attributed to the carrier-facilitated endo-lysosomal escape of DOX, which avoided exocytosis by lysosome secretion, resulting in an effective accumulation of DOX in the cytoplasm. The enhanced elimination of DOX from the MCF-7/ADR cells also accounted for the remarkable decrease in cytotoxicity against the cells of AT-M. Three micelles were further evaluated with MCF-7 cells and MCF-7/ADR-resistant cells xenografted mice model. In accordance with the in vitro results, AT-M and (endo)E-M demonstrated the strongest inhibition on the MCF-7 and MCF-7/ADR xenografted tumor, respectively. Active targeting and active targeting in combination with endo-lysosomal escape have been demonstrated to be the primary function for a nanocarrier against doxorubicin-sensitive and doxorubicin-resistant MCF-7 cells, respectively. These results indicate that the rational design of multifunctional nanocarriers for cancer therapy needs to consider the heterogeneous cancer cells and the primary function needs to be integrated to achieve effective payload delivery.